Clinical outcomes and long-term efficacy of high tibial osteotomy in treating knee instability: An updated systematic review - Mustamsir Edi; Aji Aulia Pandu; Adiwangsa Ahmad Abdilla; Akmalizzan Azfar Ahnaf (SICOT-J)
Introduction: Knee joint stability is influenced by force distribution and ligament structures. High Tibial Osteotomy (HTO) treats knee deformities and redistributes load, reducing further invasive procedures. High Tibial Osteotomy (HTO) is a well-established procedure for addressing knee instability, particularly in cases involving ligament deficiencies such as ACL and PCL insufficiencies. This systematic review aims to evaluate the clinical outcomes and long-term efficacy of HTO in improving knee stability and function. Methods: A systematic literature search was conducted using Cochrane Central, PubMed, MEDLINE, and ProQuest databases for studies published between 2000 and June 2024. Eligible studies included human subjects with at least six months of follow-up and focused on HTO for knee instability. Exclusion criteria included animal studies, non-knee joint studies, and reviews. Data on patient demographics, follow-up duration, subjective and objective outcomes, and complications were extracted. Results: Out of 536 studies identified, 11 met the inclusion criteria, encompassing 303 patients. Combining HTO with ACL or PCL reconstruction significantly improved both subjective instability and objective measures, including Lachman and Pivot Shift test grades. Patient satisfaction was high, and functional scores such as Lysholm and Tegner improved markedly. The incidence of complications was low, with minor issues such as infections and delayed union, and no reported graft failures. Conclusion: HTO, particularly when combined with ligament reconstruction, effectively treats knee instability due to ACL or PCL deficiency. The procedure demonstrates strong mid- to long-term outcomes, high patient satisfaction, and a low rate of complications. It remains a viable option for patients with knee instability.